2015
DOI: 10.1093/hmg/ddv035
|View full text |Cite
|
Sign up to set email alerts
|

Fine-mapping identifies two additional breast cancer susceptibility loci at 9q31.2

Abstract: We recently identified a novel susceptibility variant, rs865686, for estrogen-receptor positive breast cancer at 9q31.2. Here, we report a fine-mapping analysis of the 9q31.2 susceptibility locus using 43 160 cases and 42 600 controls of European ancestry ascertained from 52 studies and a further 5795 cases and 6624 controls of Asian ancestry from nine studies. Single nucleotide polymorphism (SNP) rs676256 was most strongly associated with risk in Europeans (odds ratios [OR] = 0.90 [0.88–0.92]; P-value = 1.58 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 46 publications
1
39
0
Order By: Relevance
“…Earlier breast cancer fine-mapping studies [30, 56, 6365] identified multiple candidates for causal variants, but it remains a challenge to determine the evidence required to confidently declare a variant causal. In contrast to previous studies, this is the first study, to our knowledge, to use sequence data rather than genotyped and imputed data, greatly improving genomic coverage.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier breast cancer fine-mapping studies [30, 56, 6365] identified multiple candidates for causal variants, but it remains a challenge to determine the evidence required to confidently declare a variant causal. In contrast to previous studies, this is the first study, to our knowledge, to use sequence data rather than genotyped and imputed data, greatly improving genomic coverage.…”
Section: Discussionmentioning
confidence: 99%
“…Many fine-mapping studies have identified independent effects within regions of LD [20,21] , with the proportion of such regions being reported as high as onethird [22] . Given the limited power to detect multiple independent effects, the true proportion may be higher.…”
Section: Discussionmentioning
confidence: 99%
“…One additional variant, rs11571833 at chromosome 13q13, was not genotyped and could not be imputed in all 3 studies; this variant had a minor allele frequency of 0.006 in the 1000 Genomes AFR population. These 74 risk variants include stronger markers than the index SNP found in GWAS as well as independent signals discovered through subsequent fine-mapping studies (Supplemental Table S1) (1, 3, 4, 8, 10, 11). …”
Section: Methodsmentioning
confidence: 99%